Gradient Catastrophe in the Classical Solutions of Nonlinear Hyperbolic Systems (Journal of Partial Differential Equations, 2000)
Classical solutions of hyperbolic systems, generally, collapse in finite time, even for small and smooth initial data. Here, we consider a type of these systems and prove a blow up result.
Keywords: Classical solution; blow up; strictly hyperbolic; dissipation; existence